No indications of weight gain associated DNA methylation changes in patients with anorexia nervosa - Rajcsanyi, Luisa Sophie; Kesselmeier, Miriam; Schröder, Christopher; Schmelting, Carolin; Peters, Triinu; Föcker, Manuel; Kraft, Isabelle; Beygo, Jasmin; Leitão, Elsa; Zeschnigk, Michael; Giuranna, Johanna; Herpertz-Dahlmann, Beate; et al. (Scientific reports, 2025)
Anorexia nervosa (AN) is a mental disorder marked by a significantly low body weight. Differentially methylated CpG sites have been reported to be involved in body weight regulation. Methylation pattern may change during considerable weight gain by in-patient treatment. Consequently, we aimed to (1) replicate the hypomethylation at the NR1H3 gene locus (identified in our previous epigenome-wide association study) in independent study groups of 189 female patients with AN and 67 healthy-lean female controls, and (2) identify regions associated with large weight gain associated DNA methylation changes in three patients with AN through whole-genome bisulfite sequencing in CD14+ cells. In the replication study, no evidence was observed for hypomethylation at the investigated 15 CpG sites of the NR1H3 locus. Relying on two analysis tools (camel, metilene) to identify differentially methylated regions (DMRs), subtle methylation differences concordant between both tools were detected only when the usual threshold of camel was lowered. Then, eight regions were selected exemplarily for technical replication with deep bisulfite sequencing in the same three patients with AN. None of the regions could be confirmed. Summarising, we could not confirm hypomethylation at NR1H3 and could not detect methylation differences in patients with AN between admission and weight gain at discharge.
Veröffentlicht: 07. August 2025
Gesehen am 21.01.2026